Analysis of the Effectiveness, Efficiency, and Safety of Perioperative Prophylaxis in Surgical Patients in a Multidisciplinary Hospital - T. E. Morozova; M. V. Lukina; T. B. Andrushchishina; M. A. Chukina (Антибиотики и Химиотерапия, 2020)
Objective. To evaluate the effectiveness, rationality, and safety of the use of antibacterial medications for the purpose of perioperative prophylaxis (POP) of infectious complications in patients of surgical departments in a multidisciplinary hospital.Materials and methods. A pharmacoepidemiological analysis of 576 case histories of patients aged from 18 to 87 years old (average age was (Ì±σ) 57.4±14.5), of which 347 (60.2%) were male and 229 (39.8%) — female, after surgical interventions was carried out. The frequency and nature of infectious complications, the rationality of the choice of antibiotic therapy, the incidence of adverse reactions were analyzed. Statistical analysis of the data was carried out using the statistical analysis software package STATISTICA 10.0 (StatSoftInc., USA).Results. The choice of POP schemes corresponded to the recommendations in 207 (35.9%) cases. A high level of non-compliance with the recommendations for perioperative prophylaxis (47.6%) and violations of the POP (76.2%) were revealed. The total number of cases of dosing regimens violation amounted to 225 (39.1%) cases. The frequency of infectious complications in the postoperative period was n=90 (15.6%). The study revealed the interrelationships of non-rational POP schemes with the length of stay in the ICU (p=0.003), violations of the antibiotic dosing regimens with the frequency of repeated surgical interventions associated with infection (p=0.001), the length of stay in the ICU (p=0.005), mortality rate (p=0.002), and isolation of multidrug-resistant strains (p=0.016). Renal impairment is an independent unfavorable predictor of the development of adverse reactions (p<0.0001), the development of infectious complications (p=0.006), the length of stay in the ICU (p=0.049), the length of hospitalization (p<0.001), and fatal outcome (p=0.003 ).Conclusions. Patients of surgical profile in real clinical practice maintain a high level of non-compliance with recommendations for perioperative prophylaxis, violation of POP periods and violation of antibiotic dosing regimens, which negatively affects hospital indicators (increased mortality, length of stay in ICU, frequency of repeated surgical interventions associated with infection) and increases the risk of adverse reactions development.